New Insight into Mercury Removal from Fish Meat Using a Single‐Component Solution Containing cysteine - Przemysław Strachowski; Geeta Mandava; Johan Lundqvist; Romain Bordes; Mehdi Abdollahi (Global Challenges)
Abstract A novel approach for reducing mercury content in fish meat during post‐packaging storage is developed to extend the margin of their safe consumption. It involves employing a single‐component aqueous medium containing cysteine, as the active agent responsible for displacing mercury from fish proteins and its stabilization in the medium without the need for pH adjustments. The mercury removal efficiency depends on the cysteine concentration and its ratio to fish muscle. Using 1.2 wt% cysteine enables a reduction of mercury in canned Albacore tuna by 25–35%, depending on the fish product type and the exposure time of up to 2 weeks. The potential for the successful application of the developed method in active food packaging solutions is studied for the simultaneous or subsequent purification of the extraction solution through adsorption. Using thiolated silica could potentially enable the extraction process but it is shown that the presence of cysteine significantly hinders the adsorption.